الرواة الذين قال فيهم البزار ليس بالقوي في مسنده: نماذج تطبيقية - الخزاعي, فارعه (جامعة الوادي - University of Eloued, 2021)
الملخص إن من الجهود التي بُذلت لحفظ السنة النبوية، اعتناء العلماء بنقد الرواة، والبحث في أحوالهم، ومروياتهم، وبيان مراتبهم في الجرح والتعجيل، وممن اعتنى بذلك الإمام البزار فقد هدف البحث إلى جمع الرواة الذين قال فيهم البزار(ليس بالقوي)، وبيان مراده، مع ذكر الراجح في هؤلاء الرواة، واستخدم الباحث المنهج الاستقرائي والاستنباطي. وقد خلصت الدراسة إلى النتائج التالية: 1- أن قول البزار(ليس بالقوي) في الغالب تضعيف للراوي، وقد يصل إلى الترك. 2- بلغ عدد الرواة الذين تمت دراستهم(21) راوياً 3- اختلاف مراد الأئمة في الجرح والتعديل. يوصي الباحث بإجراء مزيد من البحوث في بيان معنى (ليس بالقوي) عند العلماء، ومعرفة مقصودهم بذلك، مع جمع الرواة الذي قيل فيهم ذلك The efforts that were paid to preserve the prophetic Sunnah included the scholars' attention of criticizing the narrators and researching in their conditions, narrations and their ranks in the discrediting and endorsement. One of those whoever took care of that is Imam Al-Bazar. The current research aims at collecting the narrators whom Al-Bazar said (not strong), to explain his purpose, with mentioning the most probable of these narrators. The researcher used the inductive and deductive approach. The study concluded with the following results: 1- Al-Bazar saying (not strong) in most cases weakens the narrator and it may reach the neglecting. 2 - The number of narrators who have been studied reached (20) narrators. 3 - The difference of the Imams’ desires regarding discussion and modification. The researcher recommends conducting more researches in stating the meaning of (not strong) by scholars, and knowledge they intended meaning, with the collection of narrators in whom that wassaid
Narrators of the Prophet’s Hadith whom Al-Bazzar described in his Musnad book by saying: “He is not strong.” -"Applied Models"
مقال
Keywords: الرواة، البزار،ليس بالقوي، الحديث; the narrators ;Al bazaar; not strong;Hadith.